2011
DOI: 10.1002/bjs.7334
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three separate antiadhesive barriers for intraperitoneal onlay mesh hernia repair in an experimental model

Abstract: Prevadh and Seprafilm are potent materials for the reduction of adhesion formation. A potential relationship between effective adhesion prevention and impaired tissue integration of the implant was observed. Fibrin sealant proved an excellent agent for SAB fixation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 30 publications
0
42
0
1
Order By: Relevance
“…Considering hernia surgery, just a limited number of studies are available. Mainly biomaterials used for laparoscopic applications have been coated using this kind of materials to reduce postoperative adhesion formation, with conflicting results [121,155,156]. Murphy et al recently presented a study investigating a series of biodegradable adhesive polymers that are synthetic mimics of mussel adhesive proteins (MAPs), composed of 3,4-dihydroxyphenylalanine (DOPA)-derivatives, polyethylene glycol (PEG) and polycaprolactone (PCL) to strengthen biomaterial fixation.…”
Section: Protection Against Foreign Body Reactionmentioning
confidence: 98%
See 2 more Smart Citations
“…Considering hernia surgery, just a limited number of studies are available. Mainly biomaterials used for laparoscopic applications have been coated using this kind of materials to reduce postoperative adhesion formation, with conflicting results [121,155,156]. Murphy et al recently presented a study investigating a series of biodegradable adhesive polymers that are synthetic mimics of mussel adhesive proteins (MAPs), composed of 3,4-dihydroxyphenylalanine (DOPA)-derivatives, polyethylene glycol (PEG) and polycaprolactone (PCL) to strengthen biomaterial fixation.…”
Section: Protection Against Foreign Body Reactionmentioning
confidence: 98%
“…The rationale behind combining a mesh and an absorbable barrier is to separate the implant and viscera until the mesh becomes covered by a neomesothelium that prevents adhesion formation [125]. Many animal studies have compared coated meshes and investigated the effect of separate antiadhesive barriers [121,[126][127][128][129][130][131][132]. The overall results are somewhat conflicting, and no single mesh construction could be identified completely avoiding adhesion formation.…”
Section: Antiadhesive Barriers and Antiadhesive Mesh Coatingmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no infl ammatory reaction, and the extent and density of fi brosis were small. Three types of antiadhesive fi lms (SurgiWrap ® , Prevadh ® , and Seprafi lm ® ) were compared for intraperitoneal onlay mesh hernia repair in a rat model [ 60 ] . Prevadh (Covidien, Mansfi eld, Massachusetts) is made of oxidized bovine atelocollagen type 1, poly(ethylene glycol), and glycerol, which is degraded within 3 weeks.…”
Section: Fig 516mentioning
confidence: 99%
“…Bard Inc., Warwick, Rhode Island, USA), which minimises the attachment of peritoneal tissue (adhesions) to the prosthesis, as well as visceral erosion. The efficacy of Seprafilm TM in preventing the formation of adhesions has been widely proven, in both experimental [6][7][8] and clinical [9][10][11] studies. Indeed, a Cochrane review published in 2009 [12] concluded that: ''There is evidence that the use of hyaluronic acid/carbomethyl cellulose (HA/CMC) membrane reduces incidence, extent and severity of adhesions in the abdomen.''…”
Section: Introductionmentioning
confidence: 99%